2021
DOI: 10.4236/ajps.2021.121005
|View full text |Cite
|
Sign up to set email alerts
|

Further Insights on the <i>Datura innoxia</i> Hyoscyamine 6<i>β</i>-Hydroxylase (DiH6H) Based on Biochemical Characterization and Molecular Modeling

Abstract: Hyoscyamine, anisodamine and scopolamine are tropane alkaloids present in some Solanaceae species and used in modern medicine. L-Hyoscyamine is hydroxylated to 6β-hydroxyhyoscyamine (anisodamine) and then epoxidated to scopolamine by the dual action of hyoscyamine 6β-hydroxylase (H6H), a 2-oxoglutarate dependent dioxygenase. A natural mutation in the Gly-220 residue to Cys was previously shown to be associated with the loss of function of H6H in Mandragora officinarum, preventing the accumulation of anisodamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…Two remaining metabolites, T20 and T21, lack putative annotations (Table S8 ). Although the exact mass of T20 [M+H] + , m/z 306.1699 corresponds to C 17 H 24 NO 4 + , consistent with hydroxyhyoscyamine and hydroxylittorine, the fragment ions m/z 200.13 and 154.12 are inconsistent with this annotation as these metabolites yield m/z 158.12 and m/z 140.12 fragment ions (Schlesinger et al ., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two remaining metabolites, T20 and T21, lack putative annotations (Table S8 ). Although the exact mass of T20 [M+H] + , m/z 306.1699 corresponds to C 17 H 24 NO 4 + , consistent with hydroxyhyoscyamine and hydroxylittorine, the fragment ions m/z 200.13 and 154.12 are inconsistent with this annotation as these metabolites yield m/z 158.12 and m/z 140.12 fragment ions (Schlesinger et al ., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Two remaining metabolites, T20 and T21, lack putative annotations (Table S8). Although the exact mass of T20 [M+H] + , m/z 306.1699 corresponds to C 17 H 24 NO 4 + , consistent with hydroxyhyoscyamine and hydroxylittorine, the fragment ions m/z 200.13 and 154.12 are inconsistent with this annotation as these metabolites yield m/z 158.12 and m/z 140.12 fragment ions (Schlesinger et al, 2021). Tandem mass spectrometry of ions increased in AbPyKS-silenced plants revealed that 36 metabolites gave rise to an m/z 84.08 fragment ion (C 5 H 10 N + ) consistent with metabolites that contain a methylpyrrolidine moiety (Fig.…”
Section: Discovery Metabolomics Reveals An Increase In Pyrrolidine Al...mentioning
confidence: 99%